Benefits of specialist palliative care by identifying active ingredients of service composition, structure, and delivery model: A systematic review with meta-analysis and meta-regression. - Miriam J Johnson; Leah Rutterford; Anisha Sunny; Sophie Pask; Susanne de Wolf-Linder; Fliss E M Murtagh; Christina Ramsenthaler (PLoS Medicine)
Background Specialist palliative care (SPC) services address the needs of people with advanced illness. Meta-analyses to date have been challenged by heterogeneity in SPC service models and outcome measures and have failed to produce an overall effect. The best service models are unknown. We aimed to estimate the summary effect of SPC across settings on quality of life and emotional wellbeing and identify the optimum service delivery model. Methods and findings We conducted a systematic review with meta-analysis and meta-regression. Databases (Cochrane, MEDLINE, CINAHL, ICTRP, clinicaltrials.gov) were searched (January 1, 2000; December 28, 2023), supplemented with further hand searches (i.e., conference abstracts). Two researchers independently screened identified studies. We included randomized controlled trials (RCTs) testing SPC intervention versus usual care in adults with life-limiting disease and including patient or proxy reported outcomes as primary or secondary endpoints. The meta-analysis used, to our knowledge, novel methodology to convert outcomes into minimally clinically important difference (MID) units and the number needed to treat (NNT). Bias/quality was assessed via the Cochrane Risk of Bias 2 tool and certainty of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool. Random-effects meta-analyses and meta-regressions were used to synthesize endpoints between 2 weeks and 12 months for effect on quality of life and emotional wellbeing expressed and combined in units of MID. From 42,787 records, 39 international RCTs (n = 38 from high- and middle-income countries) were included. For quality of life (33 trials) and emotional wellbeing (22 trials), statistically and clinically significant benefit was seen from 3 months' follow-up for quality of life, standardized mean difference (SMD in MID units) effect size of 0.40 at 13 to 36 weeks, 95% confidence interval (CI) [0.21, 0.59], p < 0.001, I2 = 60%). For quality of life at 13 to 36 weeks, 13% of the SPC intervention group experienced an effect of at least 1 MID unit change (relative risk (RR) = 1.13, 95% CI [1.06, 1.20], p < 0.001, I2 = 0%). For emotional wellbeing, 16% experienced an effect of at least 1 MID unit change at 13 to 36 weeks (95% CI [1.08, 1.24], p < 0.001, I2 = 0%). For quality of life, the NNT improved from 69 to 15; for emotional wellbeing from 46 to 28, from 2 weeks and 3 months, respectively. Higher effect sizes were associated with multidisciplinary and multicomponent interventions, across settings. Sensitivity analyses using robust MID estimates showed substantial (quality of life) and moderate (emotional wellbeing) benefits, and lower number-needed-to-treat, even with shorter follow-up. As the main limitation, MID effect sizes may be biased by relying on derivation in non-palliative care samples. Conclusions Using, to our knowledge, novel methods to combine different outcomes, we found clear evidence of moderate overall effect size for both quality of life and emotional wellbeing benefits from SPC, regardless of underlying condition, with multidisciplinary, multicomponent, and multi-setting models being most effective. Our data seriously challenge the current practice of referral to SPC close to death. Policy and service commissioning should drive needs-based referral at least 3 to 6 months before death as the optimal standard of care.